Finite element analysis on transient MHD 3D rotating flow of Maxwell and tangent hyperbolic nanofluid past a bidirectional stretching sheet with Cattaneo Christov heat flux model. (1st February 2022) - Ali, Bagh; Thumma, Thirupathi; Habib, Danial; salamat, Nadeem; Riaz, Saleem
Abstract: The finite element analysis on the transient magnetohydrodynamic three-dimensional rotating flow of Maxwell and tangent hyperbolic nanofluid flow past a bidirectional stretching sheet with Cattaneo Christov heat flux model has been explored numerically. The thermophoresis and Brownian motion effects are taken into account in the flow governing boundary layer equations. Appropriate similarity transformations are applied for the principal PDEs to transform into nonlinear ODEs. A widely recognized Numerical scheme known as the Finite Element Method is employed to solve the resultant convective boundary layer balances. The portrayal of certain physical parameters on the flow model is portrayed via figures and numerical tables. The temperature and concentration distribution for tangent hyperbolic nanofluid is prominently than that of Maxwell nanofluid, but inverse trend is observed for velocities profiles. An outstanding comparison with existing literature ensures a remarkable accuracy and concludes the rate of convergence is extraordinary for nonlinear differential systems. These examinations are relevant to the field of plastic films, crystal growing, paper production, and cooling of metal sheets. Highlights: Unsteady rotating flow of Maxwell and tangent hyperbolic nanofluids is modeled. Buongiorno model for nanoparticles is taken into account for modeling. Finite element technique is implemented to solve the non-linear systems of partial differential equations. Higher inputs of the parameters for rotational fluid cause to slow the primary as well as secondary velocities.